Antarctic ecosystem responses following ice‐shelf collapse and iceberg calving: Science review and future research. (5th October 2020) - Ingels, Jeroen; Aronson, Richard B.; Smith, Craig R.; Baco, Amy; Bik, Holly M.; Blake, James A.; Brandt, Angelika; Cape, Mattias; Demaster, David; Dolan, Emily; Domack, Eugene; Fire, Spencer; et al.
Abstract: The calving of A‐68, the 5, 800‐km 2, 1‐trillion‐ton iceberg shed from the Larsen C Ice Shelf in July 2017, is one of over 10 significant ice‐shelf loss events in the past few decades resulting from rapid warming around the Antarctic Peninsula. The rapid thinning, retreat, and collapse of ice shelves along the Antarctic Peninsula are harbingers of warming effects around the entire continent. Ice shelves cover more than 1.5 million km 2 and fringe 75% of Antarctica's coastline, delineating the primary connections between the Antarctic continent, the continental ice, and the Southern Ocean. Changes in Antarctic ice shelves bring dramatic and large‐scale modifications to Southern Ocean ecosystems and continental ice movements, with global‐scale implications. The thinning and rate of future ice‐shelf demise is notoriously unpredictable, but models suggest increased shelf‐melt and calving will become more common. To date, little is known about sub‐ice‐shelf ecosystems, and our understanding of ecosystem change following collapse and calving is predominantly based on responsive science once collapses have occurred. In this review, we outline what is known about (a) ice‐shelf melt, volume loss, retreat, and calving, (b) ice‐shelf‐associated ecosystems through sub‐ice, sediment‐core, and pre‐collapse and post‐collapse studies, and (c) ecological responses in pelagic, sympagic, and benthic ecosystems. We then discuss major knowledge gaps and how science might address these gaps. This article is categorized under: Climate, Ecology, and Conservation > Modeling Species and Community Interactions Abstract : Antarctic ice‐shelf disintegration is re‐shaping the pelagic and benthic realms associated with it. Based on current knowledge, shifts will occur in oceanographic parameters, ice dynamics, and spatial and temporal ranges of organisms, populations and communities, altering predator‐prey and other trophic interactions, benthopelagic coupling, and many other ecological processes and functions, and this far beyond the immediate ice‐shelf areas. Figure adapted from Ingels et al. (2018).